Management of Vaccination Failure in a Case of HIV -HBV Co-infection: A Case Report - Small, Andre; Schroeder, Hilary; Maramraj, Raghu; Joanes, Marianinha (International Journal of Medical Students, 2014)
Background: A 60-year-old African American female patient, with chronic HIV infection since 1999, presented with markers of acute hepatities B virus (HBV) infection for the past 15 months. The patient was previously vaccinated for HBV. Immunoglobulin dysfunction was hypothesized, but electrophoresis yielded no conclusive result. Results: Investigation suggests that the patient is a non-responder: someone who fails to sero-convert to standard vaccinations. This condition can be linked to B-cell dysfunction due to chronic HIV infection. Conclusion: It is suggested that non-responders may require a 6-dose regimen to achieve sero-conversion for vaccination. Prevention of co-infection should be the mainstay of treatment, which is achieved by vaccination. However, immune system dysfunction can lead to complications.